Development of Automatic Handwashing Facilities as a Hygiene Solution at Libasuttaqwa Foundation using the PAR Approach - Ismail, Nanang; Sudirman, Eded (ELDIMAS: Jurnal Pengabdian Pada Masyarakat, 2024)
The habit of handwashing is a fundamental effort to maintain public health and hygiene, especially in busy environments such as educational institutions and places of worship. The use of automatic sensor technology can enhance water usage efficiency and promote the habit of maintaining clean and healthy behavior. In this Community Service Program (PkM), the Libasuttaqwa Foundation in Subang was selected as a partner to develop an automatic handwashing device through a University-Community Partnership (KUM) approach and the Participatory Action Research (PAR) method. Activities within PAUD, DTA, majlis ta’lim, and mosque congregations under the Libasuttaqwa Foundation require measures to maintain health by providing automatic handwashing facilities supported by technology at various activity points. The program involved planning, device development, and evaluation carried out collaboratively with the community partners. Evaluation results indicate that the device is highly beneficial in supporting public health and has the potential to be further developed for use in other public facilities. Additionally, active involvement of the partners in the development process successfully enhanced their awareness and sense of ownership of the resulting technology.   Kebiasaan mencuci tangan merupakan salah satu upaya mendasar untuk menjaga kesehatan dan kebersihan masyarakat, terutama di lingkungan dengan aktivitas padat seperti pendidikan dan tempat ibadah. Pemanfaatan teknologi sensor otomatis dapat meningkatkan efisiensi penggunaan air dan mendukung pembiasaan perilaku hidup bersih. Dalam kegiatan Pengabdian kepada Masyarakat (PkM) ini, Yayasan Libasuttaqwa di Subang dijadikan mitra untuk mengembangkan perangkat cuci tangan otomatis melalui pendekatan Kemitraan Universitas dan Masyarakat (KUM) serta metode Participatory Action Research (PAR). Aktivitas di PAUD, DTA, majlis ta’lim, dan jama’ah masjid, yang berada dalam naungan Yayasan Libasuttaqwa, perlu dijaga agar kesehatan tetap terpelihara dengan menyediakan sarana cuci tangan otomatis dengan dukungan teknologi di beberapa titik aktivitas. Kegiatan melibatkan perencanaan, pengembangan perangkat, hingga evaluasi dilakukan bersama dengan masyarakat mitra. Hasil evaluasi menunjukkan bahwa perangkat ini sangat bermanfaat dalam mendukung kesehatan masyarakat dan berpotensi dikembangkan lebih lanjut untuk memenuhi kebutuhan di sarana umum lainnya. Selain itu, keterlibatan aktif mitra dalam proses pengembangan berhasil meningkatkan kesadaran serta rasa kepemilikan terhadap teknologi yang dihasilkan